Salmonella Species Detection in Chicken Noodle Toppings Prepared by the Food Vendors around Jatinangor Campus of Universitas Padjadjaran - Zia, Luk Lee; Megantara, Imam; Suryosutanto, Suryosutanto (Althea Medical Journal, 2016)
Background: Salmonellae is Gram negative Enterobacteriaceae which are commonly found in water. It can cause diseases in human through improper hygiene and sanitation practice, contamination of poultries, cross contamination from other food during storage, and also from Salmonella species carriers. Chicken noodle toppings are usually prepared early in the morning and not heated up upon serving. There are possibilities for bacterial contamination if the food vendors lack of hygienic practices. The risk of Salmonella species contamination is increased too as it can be spread through inappropriate hygiene and sanitation. Hence, the objective of the study was to detect the presence of Salmonella species in the chicken noodle toppings prepared by the food vendors around Jatinangor Campus of Universitas Padjadjaran.Methods: A descriptive laboratory study was conducted in September 2013. A total of 44 samples of chicken noodle toppings were collected from the food vendors in Jatinangor. The samples were cultured on Salmonella-Shigella agars. Then, Gram staining and biochemical tests were performed.Results: The chicken noodle toppings were not contaminated by Salmonella species, but other bacteria species such as Klebsiella pneumoniae, Serratia, Enterobacter, Escherichia coli, and Shigella species were found.Conclusions: There is no Salmonella species found. However, there are some other bacteria found such as Klebsiella pneumoniae, Serratia, Enterobacter, Escherichia coli, and Shigella species. It means that the food vendors lack of hygienic and sanitation aspects. Thus, proper actions should be taken to educate and increase the awareness of food vendors on the importance of sanitation. [AMJ.2016;3(4):566â9]Â DOI:Â 10.15850/amj.v3n4.940